PROFITABILITY DRIVERS IN INDONESIAN ISLAMIC AND CONVENTIONAL BANKS: MACROECOOMIC AND MICROECONOMIC PERSPECTIVE - Himma, Nurrosyida Latifa; Atmanti, Hastarini Dwi (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2025)
This study investigates the impact of macroeconomic variables, namely inflation, gross domestic product (GDP), and the Bank Indonesia interest rate (BI-rate), alongside microeconomic indicators such as non-performing loans (NPL), loan-to-deposit ratio (LDR), non-performing financing (NPF), financing-to-deposit ratio (FDR), and operating expenses to operating income (OEOI) on the profitability of both conventional and Islamic banks in Indonesia over the period 2017–2023. Employing a purposive sampling technique, 7 Islamic banks and 7 conventional banks were selected from a population of 13 Islamic and 92 conventional banks, based on the criteria of complete financial disclosures and consistent financial performance. Panel data regression analysis reveals that, for conventional banks, inflation exerts a statistically significant negative influence on return on assets (ROA), whereas GDP, the BI-rate, and LDR exhibit significant positive effects. Conversely, NPL and OEOI negatively affect profitability. In the case of Islamic banks, inflation, NPF, and FDR demonstrate significant adverse impacts on ROA, while GDP, the BI-rate, and OEOI contribute positively. These findings emphasize the divergent financial structures and sensitivities of conventional and Islamic banks in response to macroeconomic and microeconomic dynamics. The study offers strategic insights for bank management and regulatory authorities to enhance policy frameworks, with particular emphasis on risk mitigation and digital adaptation, thereby fostering sustained profitability and competitiveness in Indonesia’s banking sector.